Analisis Kesuksesan Aplikasi Food Delivery Menggunakan Model DeLone & McLean: Studi Empiris Pengguna ShopeeFood - Erina Setyawati; Berlilana; Dhanar Intan Surya Saputra (Jurnal Algoritma, 2026)
The digital transformation in the food delivery industry is driving service providers to offer high-quality information systems while ensuring user security and privacy so that satisfaction levels can be maintained. This study was conducted to examine the influence of Information System Quality and Security & Privacy on User Satisfaction among ShopeeFood app users by adopting the DeLone and McLean information system success model and using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The study employed a quantitative approach by collecting data through a questionnaire distributed to 100 ShopeeFood users. The analysis results show that Information System Quality and Security & Privacy have a positive and significant influence on User Satisfaction. An R-squared value of 0.642 indicates that these two variables account for 64.2% of the variation in user satisfaction. These findings confirm that optimal information system quality, supported by adequate security and privacy protections, plays a crucial role in enhancing ShopeeFood user satisfaction. From a theoretical perspective, this study reinforces the relevance of the DeLone and McLean model in the context of digital food delivery services, while from a practical standpoint, the research findings can serve as a reference for service providers to improve system quality, service security, and the overall user experience.